2014
DOI: 10.1371/journal.pone.0111101
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Toxic Effects of the Methanol Extract of Citrus macroptera Montr. Fruit via Biochemical and Hematological Evaluation in Female Sprague-Dawley Rats

Abstract: Citrus macroptera Montr. (C. macroptera) is locally known as Satkara. The fruit of this plant is used as appetite stimulant and in the treatment of fever. This study therefore aimed to evaluate the toxic effects of the fruit extract using some biochemical and hematological parameters in rat model. The effects of methanol extract of Citrus macroptera Montr. fruit administered at 250, 500 and 1000 mg/kg body weight were investigated on hematological and biochemical parameters in Sprague-Dawley female rats. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…A cholesterol profile is often measured quantitatively to diagnose primary and secondary hyperlipoproteinemia, triglyceridemia and liver obstruction and high plasma triglyceride levels lead to a predisposition for cardiovascular disease (Zicha et al, 1999) and contribute to hypertension, obesity and diabetes mellitus (Shen, 2007). Dose-dependent reductions were observed in serum levels of TC, TG, VLDL-C and LDL-C in response to exposure to the fruit pulp, suggesting its lipid lowering activity and cardioprotective effect (Uddin et al, 2014a). Additionally, a dose-dependent incremental change in serum HDL-C was observed.…”
Section: Discussionmentioning
confidence: 99%
“…A cholesterol profile is often measured quantitatively to diagnose primary and secondary hyperlipoproteinemia, triglyceridemia and liver obstruction and high plasma triglyceride levels lead to a predisposition for cardiovascular disease (Zicha et al, 1999) and contribute to hypertension, obesity and diabetes mellitus (Shen, 2007). Dose-dependent reductions were observed in serum levels of TC, TG, VLDL-C and LDL-C in response to exposure to the fruit pulp, suggesting its lipid lowering activity and cardioprotective effect (Uddin et al, 2014a). Additionally, a dose-dependent incremental change in serum HDL-C was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The methanol extract of G. pedunculata was prepared according to a method as described by Uddin et al [12] with slight modifications. Briefly, the cleaned fresh matured fruits were thoroughly rinsed with cold sterile water.…”
Section: Methodsmentioning
confidence: 99%
“…If extract shows the toxicity in the body, it directly affects its components such as red blood cells, white blood cells, platelets and haemoglobin. The ranges of these components either decrease or increase significantly from normal.It indicated that the toxicity caused by the extract which can also affect the body immune as well function of organs (Uddin et al, 2014). Data of haematological analysis of 14 th and 28 th days were given in Table III and Table IV.…”
Section: Effect Of Aeri On Haematological Parametersmentioning
confidence: 99%